Integração Espacial Entre os Preços das Cestas Básicas da Região Nordeste do Brasil e Taxas do Mercado Financeiro - Lima, Kaliny Kélvia Pessoa Siqueira (2014)
The cost of the basic food basket influences the minimum wage of the Brazilian worker, the results of this study may, in these terms, reflect not only the behavior of basic market prices, but also the trend and behavior of the minimum wage, in addition to causal relationships and the transmission of prices between cities.Highlighting, in this context, the importance of studies that seek to verify the spatial integration between prices of basic food baskets, applied in the capitalsof Brazil.This study covers a monthly time-series of prices of the basic food baskets in the capitalsof the northeast of Brazil:Aracajú, Fortaleza, Natal, João Pessoa, Recife and Salvador and the financial market rates (interest rate, inflation rate and exchange rate) in the July 1994 to December 2013 period.The study has as central hypothesis to verify if the prices of foodstuffs, which compose the basic food basket according to Decree-Law 399/38, are integrated between the capitals in the Northeast Region of Brazil, as general objective to verifythe integration between markets of the basic food basket in the main capitals in the Northeast of Brazil, and as specific objectives to analyze causality and transmission of prices of the basic food basket in the six capitals in the Northeast of Brazil and assess causality between interest rates, inflation rates, exchange rates and prices of the basic food baskets in the six capitals in the Northeast of Brazil. The study used bivariate and multivariate analysis with causality and transmission of price methods;initially assessing stationarity with ADF and KPSS tests, co-integration with the Engle-Granger test based on Johansen, price transmission using vector error correction (VEC) models, as necessary, and finally the Granger causality test.The results from the bivariate analysis showed that the series are stationary, with the co-integration of order (I), showing the transmission of prices, through multivariate analysis, between the capitals:Salvador and Fortaleza to Aracaju, Natal, Recife and João Pessoa. For the causality test the markets that presented a cause-effect relationship were Aracajú x Salvador, and for financial market rates, the interest rate has an intense transmission of information and arbitrary operations, the exchange rate has no significant relationship and the inflation rate has causal relationship proportional to the intensity of information.